1998
DOI: 10.1007/bf02387293
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of uranium from thorium in hydrochloric acid medium by liquid emulsion membranes containing trioctylphosphine oxide

Abstract: The isolation of minor uranium concentration from thorium matrix in HC1 medium was investigated using liquid emulsion membrane (LEM) containing TOPO as carrier, Span 80 as surfactant and sodium citrate as stripping agent. The factors affecting the stability of the LEM were investigated. Different parameters affecting the permeation process were also studied. The results obtained showed that, under certain conditions it is possible to isolate ca. 98% of U(VI) (120 ppm) in 1.0M HC1 solution containing Th (1000 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It was reported that various metal ions [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were successfully extracted by liquid emulsion membranes. In this work, studies on the recovery and preconcentration of Cr (VI) from hydrochloric acid medium were carried out using liquid emulsion membrane technique.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that various metal ions [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were successfully extracted by liquid emulsion membranes. In this work, studies on the recovery and preconcentration of Cr (VI) from hydrochloric acid medium were carried out using liquid emulsion membrane technique.…”
Section: Introductionmentioning
confidence: 99%
“…Literature is available on impact of various parameters like ligand concentration, acid concentration in feed phase, viscosity of membrane, etc. on LEM extraction of U(VI) by TOPO [5][6][7][8][9][10][11][12][13][14][15][16]. Also literature is available on extraction of U(VI) by the ligands ( D2EHPA, TOPO and TOA ) using bulk liquid membrane (BLM), SLM and liquid-liquid extraction [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Emulsion liquid membranes (ELMs) specifically are widely used in different applications [3]. It is reported that various metal ions [4][5][6][7][8][9][10][11][12][13][14][15][16] are successfully extracted by emulsion liquid membranes. Few papers [17][18][19][20][21][22][23] were presented on the extraction of lanthanides by ELM.…”
Section: Introductionmentioning
confidence: 99%